The Value Relevance of Non-Financial Information to Firm Profitability: an Empirical Study on the Hypercompetitive Industry - Usman, Berto; Afandy, Chairil; Kamaludin, Kamaludin (JDM (Jurnal Dinamika Manajemen), 2022)
The purpose of this study is to examine the relationship between non-financial information and firm profitability. The data and samples were extracted from publicly listed companies (PLCs) operating in the U.S. hypercompetitive industry. The U.S. (NYSE) setting of the study was chosen due to the efficiency of its capital market. The efficiency of the NYSE can be identified from the rapid adjustment of stock price movement as a consequence of incoming new information. By employing panel data regression analysis of 83 companies spanning from 2011 to 2016 (498 firm-year observations), this study tests the relevance of firms’ non-financial on firm profitability. The findings suggest that non-financial information has shown a positive and relevant association with firm profitability. Thus, the presence of CSR reports (CSR_Rep), and high CSR performance scores (CSR_Perf) as the proxies of non-financial information is positively associated with firms’ profitability (ROA and ROE). In this regard, the company might explore the benefit of gaining a positive reputation and better business legitimacy from society as well as their stakeholders.